Analiza składu ciała w kontekście stanu funkcjonalnego mieszkańców Domów Pomocy Społecznej = Body composition analysis in the context of the functional state of the inhabitants of Social Welfare Homes - Aleksandra Radecka; Anna Karakiewicz; Iwona Bryczkowska; Anna Lubkowska (Kazimierz Wielki University, 2015)
Radecka Aleksandra, Karakiewicz Anna, Bryczkowska Iwona, Lubkowska Anna. Analiza składu ciała w kontekście stanu funkcjonalnego mieszkańców Domów Pomocy Społecznej = Body composition analysis in the context of the functional state of the inhabitants of Social Welfare Homes. Journal of Education, Health and Sport. 2015;5(7):343-352. ISSN 2391-8306. DOI 10.5281/zenodo.20152 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%287%29%3A343-352 https://pbn.nauka.gov.pl/works/585550 http://dx.doi.org/10.5281/zenodo.20152 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011-2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.06.2015. Revised 05.07.2015. Accepted: 12.07.2015.   Analiza składu ciała w kontekście stanu funkcjonalnego mieszkańców Domów Pomocy Społecznej Body composition analysis in the context of the functional state of the inhabitants of Social Welfare Homes   Aleksandra RadeckaA, B, D-F, Anna KarakiewiczA, B, Iwona BryczkowskaC, Anna LubkowskaA, D, E*   Zakład Diagnostyki Funkcjonalnej i Medycyny Fizykalnej, Pomorski Uniwersytet Medyczny, Szczecin, Żołnierska 54, 71-210 Szczecin, Polska; kierownik: dr hab. Anna Lubkowska, prof. nadzw. PUM   A - przygotowanie projektu badania, B - zbieranie danych, C - analiza statystyczna, D - interpretacja danych, E - przygotowanie maszynopisu,  F - opracowanie piśmiennictwa, G - pozyskanie funduszy, * autor do korespondencji   Adres do korespondencji: Anna Lubkowska annalubkowska@gamil.com mail: anna.lubkowska@pum.edu.pl tel. 91 4800 949   Abstrakt Starzenie jest okresem w którym zachodzi wiele zmian niejednokrotnie wpływających na stan funkcjonalny. Celem podjętych badań było określenie zależności miedzy składem ciała a stanem funkcjonalnym osób zamieszkujących Domy Pomocy Społecznej (DPS). Grupę badaną stanowiło 60 ochotników w wieku 76,9±11,9 lat, BMI 25,33 ± 5,92 kg/m2. Badanych poddano analizie składu ciała metodą bioimpedancji elektrycznej (bioelectrical impedance analysis, BIA) oraz ocenie testem SPPB (Short Physical Performance Battery), powszechnie stosowanym do oceny funkcjonalnej pacjentów geriatrycznych. Wyznaczono: wysokość i masę ciała, BMI, procentową zawartość tkanki tłuszczowej (%FM), masę tkanki tłuszczowej (FM), beztłuszczowa masę ciała (FFM) masę tkanki tłuszczowej wisceralnej (VFM), masę mięśni szkieletowych (SMM), masę tkanki kostnej (MTK), oraz całkowitą (TBW) i procentową zawartość wody (%TBW). W teście SPPB podczas 3-ech prób oceniano: utrzymanie równowagi, prędkość chodu na dystansie 3m oraz szybkość 5-krotnego wstawania i siadania na krześle. Zaobserwowano dymorfizm płciowy w składzie ciała, kobiety cechowały się wyższymi wartościami wskaźników otłuszczenia, tj. BMI (p<0,05), FM (p<0,01) oraz %FM (p<0,001) a mężczyźni wskaźników beztłuszczowych (p<0,001): FFM, SMM, MTK, TBW, %TBW. W grupie mężczyzn wykazano istotną dodatnią korelację pomiędzy testem chodu a wysokością i masą ciała, SMM, FFM i MTK. Wartości wskaźników FFM i SMM były związane z poziomem sprawności kończyn dolnych w grupie mężczyzn. Wyniki testu wstawania i siadania na krześle korelowały pozytywnie jedynie z wiekiem badanych. Zawartość beztłuszczowych komponentów ciała ma istotne znacznie dla funkcjonowania osób starszych, co należy uwzględniać w opiece instytucjonalnej. U osób w wieku podeszłym z podwyższonym BMI wartość wskaźników tłuszczowych nie wpływa istotne na sprawność ruchową.   Słowa kluczowe: skład ciała, bioimpedancja elektryczna, SPPB.     Abstract Aging is a period of many changes in the human body often affect the functional state. The aim of this study was to determine the relation between body composition and functional status of people living in the Social Welfare Department (DPS). The study group was included 60 volunteers aged 76.9 ± 11.9 years, BMI 25.33 ± 5.92 kg/m2. The subjects were analyzed body composition using bioimpedance (bioelectrical impedance analysis, BIA) and evaluation of test SPPB (Short Physical Performance Battery), commonly used to evaluate functional geriatric patients. The study group was designated: height and weight, BMI,% body fat (% of FM), fat mass (FM), fat free mass (FFM), body fat mass of visceral (VFM), skeletal muscle mass (SMM), bone mass (MTK), and total (TBW) and the percentage of water content (% TBW). In the test SPPB during the three trials evaluated: to maintain a balance, walking speed over a distance of 3 meters and a speed five times standing up and sitting down on a chair. It was observed sexual dimorphism in body composition, women had higher values of indicators of adiposity, ie. BMI (p <0.05), FM (p <0.01) and% FM (p <0.001) and non-fat indices men (p <0.001 ): FFM, SMM, ICC, TBW,% TBW. In the group of men demonstrated a significant positive correlation between gait test and the height and weight, SMM, FFM, and the MTK. FFM index values and SMM were associated with an efficiency level of the lower limbs in men. The test results getting up and sitting down on a chair positively correlated only with age. The content of fat-free body composition is crucial for the functioning of the elderly, which should be included in institutional care. In elderly patients with elevated BMI value does not affect fatty indicators relevant to mobility.   Keywords: body composition, multifrequency bioelectrical impedance, SPPB.